Membangun Kesiapan Berwirausaha Dari Penguatan Pendidikan dan Efikasi Diri - Auni Humaira Puteri; Titien Agustina; Abd. Wahab; Syamsul Adha; Mahyudiansyah, Mahyudiansyah (FKIP, Universitas Palangka Raya, 2024)
This research was conducted on students of the Indonesian School of Management (STIMI) Banjarmasin who are recipients of the Indonesian Student Business Competition Grant (KBMI) & the Student Entrepreneurship Coaching Program (P2MW) for the years 2018-2023, launched by the Ministry of Education, Culture, Research, and Technology. Entrepreneurship education is the process of instilling the spirit and essence of entrepreneurship to foster creativity and innovation in addressing problems, overcoming obstacles, managing various risks, and seizing opportunities for success. This study aims to determine the influence of Entrepreneurship Education (X1) and Self-Efficacy (X2) on Entrepreneurial Readiness (Y) among recipients of the KBMI & P2MW grants at STIMI Banjarmasin during the years 2018-2023. The population of this study consists of 39 individuals, which includes students and alumni of STIMI Banjarmasin who have previously received grants at the national level and obtained funding to develop their business ideas, with some having received grants two or three times. Since the population is less than 100, all population members are included as samples in this study. Data collection was conducted by distributing questionnaires through Google Forms, and data processing was carried out using SPSS 25. Data analysis techniques employed included Descriptive Statistical Analysis, Classical Assumption Testing, and Multiple Linear Regression Analysis.